Clara Peeters or the bussiness of silencing the silenced women - Gonzalo Les, Paula (Filanderas, 2017)
The art of Clara Peeters has been a milestone in the history of the Museo Nacional del Prado in Madrid. In collaboration with the Rockoxhuis Museum in Antwerp -where this exhibition could be seen from June 16 to October 2, 2016-, El Prado, which holds four paintings by this artist, hosted, from October 25, 2016 to February 19, 2017, which was its first shows dedicated to a female artist.